Unveiling the mechanisms between project manager leadership competencies and team performance: an empirical study - Wang, Peng; Haron, Nuzul Azam; Law, Teik Hua; Alias, Aidi Hizami; Qi, Yuewu (Emerald, 2024)
Purpose: This study aims to explore the influence of construction project manager competencies on team performance, using structural equation modeling (SEM) within the framework of social information processing theory. It investigates the multidimensional nature of project manager competencies and their impact on team processes and outcomes. Additionally, the study examines the mediating role of team processes in the relationship between competencies and team performance. Design/methodology/approach: Drawing on data collected from 483 construction professionals in China, this study uses SEM to analyze the relationships among project manager competencies, team processes and team performance. Findings: The results demonstrate a significant and positive effect of competencies on team performance. Specifically, task-related competencies directly contribute to performance, while people-related competencies enhance leader-member relations, and self-related competencies exert a gradual, cumulative influence. Moreover, the research confirms a three-factor competency structure and elucidates the nuanced mediating roles of team learning, monitoring and climate in the competency-performance relationship, shedding light on how specific competencies affect different stages of team development. Originality/value: This study contributes to project management literature by applying social information processing theory to elucidate how project managers influence team cognition through competencies. From a practical standpoint, it advocates for a competency-based approach to project manager selection and training, aiming to enhance team performance. Overall, this research advances the understanding of the intricate interplay between project manager competencies and team performance, using SEM and a theoretical perspective rooted in social information processing theory.